Answer:
3x - 21 = 3(x + 7).
Step-by-step explanation:
3x - 21 = 3(x + 7)
3x - 21 = 3x + 21
3x - 3x = 21 + 21
0 = 42
Since the two are not equal, this equation has no solution.
3x - 21 = 3(x - 7)
3x - 21 = 3x - 21
3x - 3x = -21 + 21
0 = 0
Since the two are equal, this equation has infinitely many solutions.
3x - 21 = x - 7
2x = 14
x = 7
This equation has one solution.
Since there is only one choice that makes sense, the answer won't be all of the choices.
The answer is A. 3x - 21 = 3(x + 7).
Hope this helps!